SCHOOL BRANDING BASED ON MEANINGFUL LEARNING IN PROMOTING STUDENT WELL-BEING IN ELEMENTARY SCHOOL - Sundari; Muhamad Halim Kusuma; Parjianto; Anam Sutopo; Sabar Narimo (SOSIOEDUKASI, 2026)
This study aims to analyze school branding based on meaningful learning in promoting student well-being in elementary schools. The novelty of this research lies in its integration of meaningful learning, school branding, and student well-being within a single analytical framework. This study employs a qualitative approach with a case study design. The research subjects include the principal, 8 teachers, and 12 students of SDN Bakipandeyan 01 Sukoharjo. Data were collected through observation, interviews, and documentation. Data analysis was conducted using an interactive model consisting of data condensation, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The research results show that school branding can be built through meaningful learning and contribute to realising student wellbeing in elementary schools. In-depth, contextual, and sustainable learning processes shape the school's image as a learning environment that supports the realisation of student wellbeing (student voice, sense of belonging, positive relationships, participation in school life, and feeling valued and respected). Thus, strengthening school branding is not only through image building but also grows from the learning experiences that students actually feel. Therefore, teachers and schools need to optimise the learning process to strengthen branding and student wellbeing.